2014
DOI: 10.1002/jbm.a.35316
|View full text |Cite
|
Sign up to set email alerts
|

β2integrins (CD11/18) are essential for the chemosensory adhesion and migration of polymorphonuclear leukocytes on bacterial cellulose

Abstract: Bacterial cellulose (BC) has been studied widely for applications in biomedical materials such as prosthetic artificial blood vessels owing to its unique characteristics, which include nontoxicity and nonimmunogenicity as compared with synthetic biopolymers such as expanded polytetrafluorethylene (ePTFE). However, to date, studies on the relative effect of leukocytes on BC as a prosthetic vascular graft are insufficient. Polymorphonuclear leukocytes (PMN) play a pivotal role in early-phase immune response to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The phenotypic analysis of peritoneal macrophages showed a high percentage of cells positive for CD11b and CD45, confirming that the peritoneal population analyzed was composed of macrophages. CD11b belongs to the integrin β2 family and plays an important role in the migration of macrophages ( 65 ), while CD45, a protein tyrosine phosphatase expressed on all cells of hematopoietic origin, is associated with the adhesion process ( 66 ). The reduction in the amount of these superficial molecules observed in both the EV Y and control groups may be related to the internalization mechanisms of these molecules in activated macrophages ( 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…The phenotypic analysis of peritoneal macrophages showed a high percentage of cells positive for CD11b and CD45, confirming that the peritoneal population analyzed was composed of macrophages. CD11b belongs to the integrin β2 family and plays an important role in the migration of macrophages ( 65 ), while CD45, a protein tyrosine phosphatase expressed on all cells of hematopoietic origin, is associated with the adhesion process ( 66 ). The reduction in the amount of these superficial molecules observed in both the EV Y and control groups may be related to the internalization mechanisms of these molecules in activated macrophages ( 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…Then 3 uL of bacteria were stabbed into 0.4 % MH agar and plates were incubated at 42°C under microaerobic conditions for 24 h. From each plate, motility was scored by measuring growth diameter (mm). Assays were repeated at least three times with three technical replicates and the results were averaged (Kim et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…A previous study suggested that disturbed activation of the Rac-ERK pathway and PI3K is responsible for the aberrant IL-8/CXCL8-induced migration in MDS (14). It has been reported that CD18 plays a critical role regarding fMLF-induced migration (15), and that expression of the CD11b-CD18 complex is decreased in MDS neutrophils (16). When stimulated with fMLF, activation of ERK1/2 and protein kinase B (PKB/Akt) was also attenuated in MDS (17).…”
mentioning
confidence: 98%